IMPLEMENTATION OF LEADERSHIP COMPETENCY OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN DEVELOPING ISLAMIC CULTURE IN SMP MUHAMMADIYAH 1 KLATEN - Widyaningrum, Widyaningrum; Istanto, Istanto (Muhammadiyah University Press, 2019)
In this day and age the noble character of a person wears off, so it is necessary to make improvements, one of which can be done through the field of education in schools. In SMP Muhammadiyah 1 Klaten the cultivation of noble character can be done through Islamic culture in schools. Here Islamic Religious Education teachers with their leadership competencies play an important role in the formation and development of Islamic culture in schools. There are still some Islamic Religious Education teachers who are less concerned about the leadership competencies that they must possess. So that the inculcation and development of the leadership spirit of a teacher of Islamic Education is very necessary to do because it can affect the success of a school in developing Islamic culture. Based on the background of the problem, the problem formulation was obtained, namely how the implementation of leadership competencies of Islamic Religious Education teachers in SMP Muhammadiyah 1 Klaten and how Islamic Religious Education teachers developed Islamic culture in SMP Muhammadiyah 1 Klaten. This study aims to describe the implementation of leadership competencies of Islamic Education Teachers in Muhammadiyah 1 Klaten Middle School and to describe Islamic Religious Education Teachers in developing Islamic culture in Muhammadiyah 1 Klaten Middle School. This type of research is field research using a qualitative approach. The method for data collection is the interview, documentation and observation. The data analysis technique is done through the stages of data reduction, data display and conclusion drawing. Based on the results of the analysis of research data, it can be concluded that: Islamic Religious Education Teachers at SMP Muhammadiyah 1 Klaten have implemented their leadership competencies both in learning and outside learning. The Teacher of Education has made plans, organized, became an innovator, motivator, facilitator, mentor and counselor, as well as guarded, controlled, and directed every activity. So that it is in accordance with Regulation of the Minister of Religion of the Republic of Indonesia number 16 of 2010 concerning the management of religious education in schools. In developing Islamic culture in SMP Muhammadiyah 1 Klaten Islamic Religious Education teachers through every religious activity carried out always exemplifies, motivates or encourages, and enforces discipline and witnesses for students who violate the rules that have been made so that Islamic activities can be well entrenched in junior high Muhammadiyah 1 Klaten and formed the noble character of students.